The Effect of Blended Learning Approach and Visual-Spatial Ability on Learning Outcomes - Bambang Setiyo HP; Hartati Mochtar; Atwi Suparman (STKIP Singkawang, 2020)
The purpose of this study was to conduct an empirical study to find out the aspects that influence the basic CNC learning outcomes, in this case regarding the application of the approach blended learning, and the abilities visual-spatial possessed by students who take the course. Based on the types of research variables that exist, then this experimental research is appropriate to be carried out using the experimental Treatment by Level design. Data analysis in this experimental study used 2-way ANOVA with one treatment variable and one attribute variable. This research was carried out using experimental research methods. This research was conducted at the CNC/CADCAM Laboratory, Department of Mechanical Education, Faculty of Engineering, Yogyakarta State University. Research Results 1) Basic CNC learning outcomes of students who take part in learning using the approach Blended Learning higher than students who take learning using the Conventional Approach; 2) Basic CNC learning outcomes of students with ability spatial-visual high, higher than students with abilities spatial-visual low who jointly follow Basic CNC learning; 3) There is an influence of the interaction between learning approaches and spatial visual abilities on basic CNC learning outcomes; 4) Basic CNC learning outcomes of students capable of high spatial visuals who take part in learning with approach blended learning, higher than students with high spatial-visual abilities who follow learning with conventional approaches; 5) Basic CNC learning outcomes of students with low spatial-visual abilities who take part in learning with approach blended learning, lower than students with low spatial-visual abilities who follow learning with conventional approaches. The conclusion of this research is the basic CNC learning outcomes of students who take part in learning using the Approach Blended Learning higher than students who take learning using the Conventional Approach.